Vapours of US and EU Market Leader Electronic Cigarette Brands and Liquids Are Cytotoxic for Human Vascular Endothelial Cells - Putzhammer, Raphaela (PLoS One, 2016)
The present study was conducted to provide toxicological data on e-cigarette vapours of different e-cigarette brands and liquids from systems viewed as leaders in the e-cigarette market and to compare e-cigarette vapour toxicity to the toxicity of conventional strong high-nicotine cigarette smoke. Using an adapted version of a previously constructed cigarette smoke constituent sampling device, we collected the hydrophilic fraction of e-cigarette vapour and exposed human umbilical vein endothelial cells (HUVECs) to the mixture of compounds present in the vapour of 4 different single-use e-cigarettes, 6 different liquid vapours produced by the same refillable e-cigarette, and one e-cigarette with an exchangeable liquid cartridge. After incubation of cells with various concentrations and for various periods of time we analysed cell death induction, proliferation rates, the occurrence of intra-cellular reactive oxygen species, cell morphology, and we also measured e-cigarette heating coil temperatures. Overall, conventional cigarette smoke extract showed the most severe impact on endothelial cells. However, some e-cigarette vapour extracts showed high cytotoxicity, inhibition of cell proliferation, and alterations in cell morphology, which were comparable to conventional high-nicotine cigarettes. The vapours generated from different liquids using the same e-cigarette show substantial differences, pointing to the liquids as an important source for toxicity. E-cigarette vapour-mediated induction of oxidative stress was significant in one out of the 11 analysed vapours. There is a high variability in the acute cytotoxicity of e-cigarette vapours depending on the liquid and on the e-cigarettes used. Some products showed toxic effects close to a conventional high-nicotine cigarette. Liquid nicotine, menthol content, and the formation of acute intracellular reactive oxygen species do not seem to be the central elements in e-cigarette vapour toxicity.